Semi-solid processing of alloys and composites XIII : selected, peer reviewed papers from the 13th International Conference on Semi-Solid Processing of Alloys and Composites (S2P 2014), September 15-17, 2014, Muscat, Sultanate of Oman - Modigell, Michael (Diffusion and defect data. Solid state phenomena, 2015)
Collection of selected, peer reviewed papers from the 13 th International Conference on Semi-Solid Processing of Alloys and Composites (S2P 2014), September 15-17, 2014, Muscat, Sultanate of Oman. The 68 papers are grouped as follows: Chapter 1: Material Development and Characterisation, Chapter 2: Rheology, Modelling and Simulation, Chapter 3: Process Development, Chapter 4: Industrial Application.